Pelatihan Kewirausahaan Dalam Pengembangan Umkm Di Masa Pandemi - Anggita, Fillia; Zailani, Zailani (Rifa'Institute, 2021)
As we know, the MSME business is one of the sectors most affected by the COVID-19 outbreak. The impact of the pandemic has resulted in many workers being forced to stay home. During the pandemic, there was a change in the consumption pattern of people's goods and services from offline to online. Many MSME actors have difficulty in achieving the targets that must be achieved when the economy is disrupted. This change in pattern, followed by Micro, Small and Medium Enterprises (MSMEs) in order to survive, and can develop so that they are able to face new normal conditions, Digitalization has become an important necessity, as evidenced by the Large-Scale Social Restriction Period (PSBB) which has increased the utilization of e-learning, eCommerce, digital literacy, delivery requests, and the need for medical/cleaning equipment, however, cannot deny the existence of the problem of digitizing MSMEs. In some remote areas, limited internet access is still an obstacle. The understanding of MSME actors towards technology, limited online marketing, production processes and online market access are still considered not optimal enough. Furthermore, consumers still feel insecure in conducting digital transactions. The purpose of this research is to overcome these problems, and help residents through the program